The optimal time window of visual-auditory integration: a reaction time analysis - Colonius, Hans; Diederich, Adele (Frontiers in Integrative Neuroscience, 2010)
The spatiotemporal window of integration has become a widely accepted concept in multisensory research: crossmodal information falling within this window is highly likely to be integrated, whereas information falling outside is not. Here we further probe this concept in a reaction time context with redundant crossmodal targets. An infinitely large time window would lead to mandatory integration, a zero-width time window would rule out integration entirely. Making explicit assumptions about the arrival time difference between peripheral sensory processing times triggered by a crossmodal stimulus set, we derive a decision rule that determines an optimal window width as a function of (i) the prior odds in favor of a common multisensory source, (ii) the likelihood of arrival time differences, and (iii) the payoff for making correct or wrong decisions; moreover, we suggest a detailed experimental setup to test the theory. Our approach is in line with the well-established framework for modeling multisensory integration as (nearly) optimal decision making, but none of those studies, to our knowledge, has considered reaction time as observable variable. The theory can easily be extended to reaction times collected under the focused attention paradigm. Possible variants of the theory to account for judgments of crossmodal simultaneity are discussed. Finally, neural underpinnings of the theory in terms of oscillatory responses in primary sensory cortices are hypothesized.